Feasibility of neurosonography in CHD-fetuses and controls in a clinical tertiary setting - Sheila M. Everwijn; Jiska F. van Bohemen; Fenna A. Jansen; Sylke J. Steggerda; Aalbertine K. Teunissen; Monique C. Haak (Elsevier, 2024)
Objective: Ultrasonographic examination is the first-tier test to detect abnormal development of central nervous system (CNS). In optimal conditions, neurosonography can detect all important hallmarks of CNS development. It is, however, not known how the performance of this modality is in a routine setting. We aimed to evaluate the feasibility of neurosonography in a time-limited routine setting. Study design: We have performed a prospective study in which we have included a group of pregnant women carrying a fetus with an isolated congenital heart defect (CHD), and a control group of fetuses without structural anomalies. We have performed basic neurosonography examination according to the guideline 'how to perform a basic screening examination of the CNS', published by the international society of ultrasound in obstetrics and gynecology in both groups. In all these examinations, 9 brain structures were scored in 3 different planes, by researchers that were blinded for group allocation. A sufficient neurosonogram was performed when 7 or more out of 9 CNS structures were clearly visible during the off-line scoring of the examination. Results: A total of 574 neurosonographic examinations were performed in 151 fetuses, 90 in the CHD-group and 61 in the control group. A sufficient neurosonogram could be performed in 79% (234/294) of cases in a clinical setting (CHD cases) and in 90% (253/280) of control pregnancies. Higher maternal BMI (>30), maternal age, fetal cephalic position, fetal gender and placental position did not significantly influence neurosonography scores. Conclusion: In clinical setting, basic fetal neurosonography can be sufficiently performed in the majority of cases. This was not significantly influenced by maternal or fetal factors. The optimal gestational age for neurosonography is between 22 and 34 weeks.